Effect of Prebiotics-Enhanced Probiotics on the Growth of Streptococcus mutans - Santichai Nunpan; Chatrudee Suwannachart; Kornchanok Wayakanon (International Journal of Microbiology)
Streptococcus mutans predominantly creates an acidic environment in an oral cavity. This results in dental demineralization and carious lesions. The probiotics are beneficial microorganisms that modulate the bacterial balance in the digestive system. Prebiotics are defined as nondigestible oligosaccharides that are utilized for the selective stimulation of the beneficial microorganisms. The objective of this study was to evaluate the efficacy of the prebiotics, galactooligosaccharides (GOS) and fructooligosaccharides (FOS), for enhancing the probiotic Lactobacillus acidophilus ATCC 4356, for inhibiting Streptococcus mutans (A32-2) for the prevention of dental caries. The growth rate of the S. mutans significantly decreased when cocultured with L. acidophilus in the GOS-supplemented medium at 3%, 4%, and 5%. In the FOS-supplemented medium, the growth rate of S. mutans significantly decreased in all concentrations when cocultured with L. acidophilus. There was no significant difference in the growth rate of L. acidophilus in all concentrations of either GOS or FOS. It can be concluded that the growth rate of S. mutans was significantly retarded when cocultured with L. acidophilus and the proper concentration of prebiotics. These prebiotics have potential for a clinical application to activate the function of the naturally intraoral L. acidophilus to inhibit S. mutans.